Self-Interested Giving: The Relationship Between Conditional Gifts, Charitable Donations, and Donor Self-Interestedness - Chao, Matthew; Fisher, Geoffrey (Management Science, 2022)
Nonprofits regularly use conditional “thank you” gifts to entice prospective donors to give, yet experimental evidence suggests that their effects are mixed in practice. This paper uses multiple laboratory experiments to test when and why thank you gifts vary in effectiveness. First, we demonstrate that although gifts often increase donations to charities that donors did not rate highly, many of the same gifts had no effects or negative effects for charities that prospective donors already liked. We replicate these findings in a second experiment that uses a different range of charity and gift options as well as different measures of participant perceptions of a charity. We also find that making gifts optional, as is common in fundraising campaigns, does not eliminate these negative gift effects. In additional experiments, we directly test for donor motives using self-report and priming experiments. We find that thank you gifts increase (decrease) the weight that donors place on self-interested (prosocial) motives, leading to changes in donation patterns. Altogether, our results suggest that practitioners may find gifts more useful when appealing to donors not already familiar with or favorably inclined to their charity, such as during donor acquisition campaigns. They may be less useful when appealing to recent donors or others who already favor the charity, in part because the gift may activate mindsets or norms that emphasize self-interested motives instead of more prosocial, other-regarding motives. This paper was accepted by Yan Chen, decision analysis.